ASSESSMENT OF HIGH MOLECULAR WEIGHT PROTEINS IN SELECTED INDIGENOUS BREAD WHEAT VARIETIES OF PAKISTAN - KHAN , TN; RASHID , K; QAMAR , M; SOHAIL , M; ABBAS , SH; WAQAR , S; SHAKOOR , A; HUSSAIN , I; ARSHAD , M; USMAN , M; IQBAL , H; VASEER , SG; et al. (Biological and Clinical Sciences Research Journal, 2024)
Higher molecular weight gluten subunits (HMW-GS) articulate variation in allelic frequency, reflecting a strong correlation with bread quality. In order to determine this quality trait, 23 different Pakistani indigenous wheat varieties were screened that may be used as selection criteria in a breeding program. For detecting variations in HMW-GS, sodium dodecyl sulfate acrylamide gel electrophoresis was used. In all, 77 Glu-1 were identified including 25 at Glu-A1, 26 at Glu-B1 and 26 at Glu-D1. Alleles at Glu-1 were 2* with a frequency of 53.3% and N with 60% frequency at Glu-A1, 6+8 with 60%, 17+18 with 45 % at Glu-B1 and 5+10 with 60% and 72% at Glu-D1. The highest frequency of subunits 20 and 5+10 were found at Glu-B1-e and Glu-D1 (a), followed by a frequency of 2* and Null at Glu-A1 (b, c), which is then followed by 2+12 at GluD-1 (a). The lowest frequency of 13+16, 17+18 and 6+8 were observed at Glu-B1 (f, i, d), respectively. Glu-A1, Glu-B1, and Glu-D1 alleles showed genetic index (i.e. 0.587, 0.54), (0.587. 0.065 and 0.48, 0.39, respectively) with an average of 0.55 and 0.37. The glu-D1 locus has a lower genetic index comparatively. The composition N, 20, 5+10 was found in maximum number (4) in Fakhr-e-Sarhad, Pasban, Pirsabak-2004 and Tatara genotypes, followed by the composition of 2*, 20, 2+12 in one check (Marvi-2000) and two varieties i.e. Chakwal-97 and Bakhtawar-92. The results describing the allelic frequency and composition of bread wheat would benefit further breeding plans for wheat to select good quality parameters.